Digital and nurse-led support intervention in primary care during the first year after curative intent treatment for breast or prostate cancer: study protocol of two cluster randomised controlled pilot trials - Kay Sundberg; Åsa G Craftman; Ann Langius-Eklöf; Linda Gellerstedt; Nazmije Kelmendi; Kristina Rooth; Tina Gustavell (BMJ Open)
Introduction The period directly after primary treatment for breast or prostate cancer is a time when patients feel unprepared about how to manage life and address unexpected health challenges. Supportive care should focus on identifying symptoms and concerns and involving survivors in their self‐care. Interventions using a blended model encompassing remote and in-person components may inform how supportive care can be organised. This protocol describes two pilot randomised controlled trials with the aim to investigate the acceptability, feasibility and potential effects of a 6 month digital and nurse-led support intervention in primary care for patients with breast or prostate cancer during the first year after primary treatment.Methods and analysis Two cluster randomised pilot trials including patients with breast or prostate cancer during the first year after ending primary treatment will run from 2023 in primary care centres in Region Stockholm. The trials will have an estimated sample size of 20 patients in each arm. The intervention groups receive a digital and nurse-led support intervention in combination with standard care, and the control groups receive standard care alone. To assess acceptability and feasibility, the participants in the intervention groups and the study nurses will be interviewed. Furthermore, digitally logged data and field notes by study-specific nurses will be analysed. Data collection for the potential effects of the intervention is conducted through self-reported standardised and validated questionnaires at baseline, and at 3, 6, 12, 18 and 24 months. Data entry and analyses will be blinded to the researchers. Qualitative data will be analysed with content analysis, quantitative data will be evaluated by comparing changes within and between groups.Ethics and dissemination This project was reviewed and approved by the Swedish Ethical Review Authority. Study results will be published in peer-reviewed journals and presented at scientific and professional meetings.Trial registration numbers ClinicalTrials.gov, NCT06471452 and NCT05100121.